2010
DOI: 10.3109/08958378.2010.504243
|View full text |Cite
|
Sign up to set email alerts
|

High aspect ratio materials: role of surface chemistry vs. length in the historical “long and short amosite asbestos fibers”

Abstract: In nanotoxicology the question arises whether high aspect ratio materials should be regarded as potentially pathogenic like asbestos, merely on the base of their biopersistence and length to diameter ratio. A higher pathogenicity of long asbestos fibers is associated to their slower clearance and frustrated phagocytosis. In the past decades, two amosite fibers were prepared and studied to confirm the role of fiber length in asbestos toxicity. Long fiber amosite (LFA) and short fiber amosite (SFA) have here bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 64 publications
6
39
0
Order By: Relevance
“…Similar to what is observed for other minerals with redox-active TMI (e.g., asbestos- Tomatis et al, 2010;Turci et al, 2013), the reactivity of JSC-1A-vf toward C-H bond in the presence of AA is largely increased with respect to experiments carried out in a nonreducing environment (phosphate buffer only). Such an increased reactivity indicates that redox-active TMI-likely iron-at the surface of JSC-1A-vf minerals are easily reduced and their radical reactivity enhanced.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar to what is observed for other minerals with redox-active TMI (e.g., asbestos- Tomatis et al, 2010;Turci et al, 2013), the reactivity of JSC-1A-vf toward C-H bond in the presence of AA is largely increased with respect to experiments carried out in a nonreducing environment (phosphate buffer only). Such an increased reactivity indicates that redox-active TMI-likely iron-at the surface of JSC-1A-vf minerals are easily reduced and their radical reactivity enhanced.…”
Section: Discussionsupporting
confidence: 73%
“…Surface iron sites are activated following reduction by AA and become the active center for the release of carbon-centered radicals (Martra et al, 2003;Tomatis et al, 2010). To explore the occurrence of such redox sites in JSC-1A-vf, AA (3 mM) was added to the buffered suspension of JSC-1A-vf containing the formate anion and the spin trapping (DMPO).…”
Section: Effect Of Aa On the Cleavage Of C-h Bondmentioning
confidence: 99%
“…There have been suggestions that CNTs can undergo a degree of dissolution depending on their form 42,43 ; thus, the retention/translocation kinetics of long CNTs from the pleural space could change over time if the CNTs undergo any biodissolution. Recently, Tomatis et al 44 reported that the greater toxicity of long asbestos fibers when compared with short asbestos fibers could be attributed to several factors other than length, including greater free radical production and reactive surface. Although these factors may give added toxicity to any fiber, we contend that the properties defined by the fiber pathogenicity paradigm (ie, length, thinness, and biopersistence) remain the primary attributes that a fiber must possess to elicit a pathogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…18 In particular, the cells internalize nutrients and signaling molecules to obtain energy and interact with other cells, respectively. The endocytosis pathways are typically classified into clathrin-and caveolaemediated endocytosis, phagocytosis, macropinocytosis, and pinocytosis ( [19][20][21] These endocytosis pathways are the most important pathways for the internalization of nanoparticles into cells because the nanoparticles are directly coated with the plasma proteins when exposed to physiological solutions. The phagocytosis pathway is used when phagocytic cells internalize foreign materials with sizes larger than 0.5 μm.…”
Section: Nanoparticle Endocytosis Endocytosis Mechanismmentioning
confidence: 99%